Fluoroscopy Guided Minimally Invasive Swine Model of Myocardial Infarction by Left Coronary Artery Occlusion for Regenerative Cardiology - Thankam, Finosh G; Radwan, Mohamed; Keklikian, Angelo; Atwal, Manreet; Rai, Taj; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2022)
Background: Despite the recent advancements in the cardiac regenerative technologies, the lack of an ideal translationally relevant experimental model simulating the clinical setting of acute myocardial infarction (MI) hurdles the success of cardiac regenerative strategies. Methods: We developed a modified minimally invasive acute MI model in Yucatan miniswine by catheter-driven controlled occlusion of LCX branches for regenerative cardiology. Using a balloon catheter in three pigs, the angiography guided occlusion of LCX for 10-15 minutes resulted in MI induction which was confirmed by the pathological ECG changes compared to the baseline control. Results: Ejection fraction was considerably decreased post-procedure compared to the baseline. Importantly, the highly sensitive MI biomarker Troponin I was significantly increased in post-MI and follow-up groups along with LDH and CCK than the baseline control. The postmortem infarct zone tissue displayed the classical features of MI including ECM disorganization, hypertrophy, inflammation, and angiogenesis confirming the MI at the tissue level. Conclusions: The present model possesses the advantage of minimal mortality, simulating the pathological features of clinical MI and the suitability for injectable regenerative therapies suggesting the translational significance in regenerative cardiology.